Cover Feature: A Review on the Current Progress and Challenges of 2D Layered Transition Metal Dichalcogenides as Li/Na‐ion Battery Anodes (ChemElectroChem 13/2021). Issue 13 (2nd June 2021) - Sahoo, Ramkrishna; Singh, Monika; Rao, Tata Narasinga
Abstract : The Cover Feature illustrates the advancement of the metal‐ion battery (Li/Na‐ion) using different transition metal dichalcogenides (TMDs) as anode material. Multi‐electron transfer reaction and unique physico‐chemical properties will be the highlight for TMDs as alternative anode material for future rechargeable battery. More information can be found in the Review by R. Sahoo et al .